Resistência de união ao microcisalhamento de sistemas adesivos autocondicionates com graus de acidez distintos: efeito de diferentes tratamentos em substrato dentinário normal e hipermineralizado artificialmente - Piccioni, Máyra Andressa Rodrigues Valinhos [UNESP] (2014)
The aim this work, divided in three studies, was evaluate the bond strength of different adhesive systems with different degrees of acidity, to different dentinal treatments: acid etching, laser and diamond bur in normal dentin and artificially hypermineralized dentin. In the first study, it was performed a literature review on the use of the Er,Cr : YSGG in Restorative Dentistry. In the second and third, two hundred twenty-four (n = 224) human molars were selected. The teeth had their third occlusal sectioned in order to expose flat dentin surface and it were ground to expose dentin surface uniform, standardized. The specimens were randomly divided into two groups according to the type of dentin normal (N /n = 108) and artificially hypermineralized (H / n = 116) . The group H received treatment for hypermineralization and eight teeth were randomly selected and observed by SEM to confirm the hypermineralization procedure. The teeth of each group were randomly divided into four different subgroups, according to the adhesive system used: Clearfil S3 Bond and Optibond All in One – One step- (Article 2 ); Clearfil SE Bond and AdheSE - Two steps - (Article 3). Each subgroup (n = 9) received different treatments: (1) conventional conditioning : application of the adhesive system according to the manufacturer’s recommendations, (2) conditioning of the dentin surface with Er,Cr:YSGG laser (Waterlase Millennium Biolaser Technology, San Clement, CA, USA) + adhesive system according to the recommendations of the manufacturer, (3) roughening of the dentin surface with a diamond tip 3098 + adhesive system according to the recommendations of the manufacturer. Then, cylindrical transparent molds were placed on the dentin surface treated with the adhesives and were filled with composite resin (Z350 XT FiltekTM - 3M ESPE) and light-cured for 40s. The molds were removed to expose the composite resin cylind...